THE IMPACT OF CORRUPTION ON FOREIGN DIRECT INVESTMENT INFLOWS: EMPIRICAL EVIDENCE FROM 64 DEVELOPING COUNTRIES (Scientific Journal of Actuarial Finance and Accounting, 2024)
The research project aims to test the impact of corruption on the net FDI (foreign direct investment) inflows across 64 developing countries between 2007 and 2023. The main hypothesis of this study is that the increase in corruption rate leads to a decline in FDI level. Moreover, corruption causes uncertainty by creating additional cost for business activities and hinders fair competition for possible foreign entrants. This empirical research project can assist countries pursuing to increase FDI and, thus, decrease poverty and stimulate growth.